Faktor-Faktor Yang Mempengaruhi Optimalisasi Pengelolaan Wakaf Produktif Pada Badan Wakaf Indonesia Di Provinsi Riau - Haniah Lubis; Tun Rustam; Nuryanti Nuryanti; Dhona Siwi Kafnaeni (Universitas Islam Negeri Sumatera Utara, 2023)
This study aims to examine in depth the factors that influence the optimization of productive waqf management at the Indonesian Waqf Board, especially in Riau Province. This research is descriptive and qualitative in nature with information retrieval using purposive sampling, namely waqf managers, especially BWI Riau Province. The data collection is through observation, interviews and Focus Group Discussion (FGD). The results of the study show that the factors influencing the optimization of productive waqf management at the Indonesian Waqf Board of Riau Province come from internal and external factors. The internal factors that directly or indirectly influence it are nazhir and managers or management of productive waqf assets. A professional nazhir must have competence, certification, and reputation, serve, be open, honest and nazhir and work full time. Management of productive waqf assets is carried out through fundraising (fundraising), landing (distribution of funds), managerial, reporting of waqf assets, normative management ethics, promotion and marketing, as well as audit activities. While the external factors that influence waqf management include society, regulations, media access, government, academics and Bank Indonesia.